Case-study: Energy expenditure of a world class male wheelchair tennis player during training, Grand Slam and British Open tournaments measured by doubly labelled water - Ellis, D. G.; Speakman, J.; Hambly, C.; Cockram, A.; Morton, J. P.; Close, G. L.; Donovan, T. F. (International Journal of Sports Science & Coaching, 2023)
The assessment of total energy expenditure (TEE) is imperative to ensure appropriate fuelling during competition and training, although the current lack of TEE research in para sport make the prescription of nutritional strategies challenging. This study aimed to assess TEE of an elite wheelchair tennis (WT) player during training and competition of the highest level. One male WT player (age 23.6 years; career high World No. 1; body mass 65.7 kg; VO2max, 45.3 ml.kg-1.min-1) participated. Prior to the assessment, VO2max and maximum heart rate, resting metabolic rate, 10 m sprint speed and upper body skinfold measurements were made. Doubly labelled water assessed TEE during a 19-day period which included the Wimbledon Championships (5 days-3 matches), training (8 days) and the British Open (BO) (6 days-7 matches). Throughout data collection, the participant continued their usual training and preparation. During Wimbledon, TEE was 3118 kcal·d-1: 60.3 kcal·kg-1 FFM: PAL 2.0 and during BO was 3368 kcal·day-1: 65.1 kcal·kg-1 FFM: PAL 2.2. Mean daily activity was 124 mins and 132 mins, respectively. During training, TEE was 3177kcal·day-1: 61.4kcal·kg-1 FFM: PAL 2.0: mean daily activity was 138 mins. These findings show the TEE of an elite WT player captured during a period of training and high-level competition, alongside data outlining the physiological profile of a world-class para-athlete.